Teoría de crecimiento económico: un debate inconcluso - Rosende, Francisco (Estudios de Economía, 2016)
This paper provides a wide-ranging overview of recent research in economicgrowth theory that emphasizes the importance of the response of economicgrowth process to changes in global productivity (GP). The research agendafor the next years should be oriented towards the elaboration of a satisfactorytheory of GP changes. This requires a consensus on the methodology used tomeasure it.